3D bioprinting of a gradient stiffened gelatin–alginate hydrogel with adipose-derived stem cells for full-thickness skin regeneration. Issue 13 (15th March 2023) - Ma, Yuan; Wang, Yilin; Chen, Danni; Su, Ting; Chang, Qiang; Huang, Wenhua; Lu, Feng
Abstract : 3D bioprinting of a gradient-stiffened gelatin–alginate hydrogel accelerated wound healing by promoting the proliferation, migration, and paracrine secretion of encapsulated ADSCs. Abstract : Current hydrogel-based scaffolds offer a promising approach to accelerate tissue regeneration, but great challenges remain in developing platforms that mimic the physical microenvironment of tissues combined with therapeutic biological cues. Here, a 3D bioprinting gelatin–alginate hydrogel for the construction of gradient composite scaffolds that mimic the dermal stiffness microenvironment was developed for architecture construction by extruding the bioink on calcium-containing substrates to achieve gradient secondary cross-linking, meanwhile, adipose-derived stem cells were encapsulated in the present hydrogels for therapeutic purposes. The gradient-stiffness scaffold exhibited good stability and biocompatibility as well as enhanced proliferation and migration of the adipose-derived stem cells. In addition, the promoted angiogenesis and healing efficiency was demonstrated via the animal wound model and was mainly attributed to the enhanced paracrine secretion of adipose-derived stem cells by the physical microenvironment provided within the gradient stiffness scaffold. The current 3D printed gradient scaffolds provide adipose-derived stem cells with a distinct yet successive architecture rather than the typical uniform microenvironment to accelerate skin regeneration, which may have broader applications in other chronic wounds or tissue defects.